The Effect of Demonstration Method on Students’ Learning Activeness in Fiqh at MTs Muallimin UNIVA Medan - Tasya Fitricia Br Sinaga (Sufiya Journal of Islamic Studies, 2024)
This study aims to determine the effect of the application of the demonstration method on the learning activity of students in Fiqh subjects in grade VII MTs Muallimin UNIVA Medan. The study used a quantitative approach with data collection techniques through a closed questionnaire distributed to 39 respondents. The research instrument was compiled based on the Likert scale and tested using the SPSS version 29 program through validity, reliability, normality, and determination coefficient tests. The results of the analysis showed that the application of the demonstration method was in the very high category with a score of 83.48%, and the student learning activity was also classified as very high with a score of 85.33%. The value of the correlation coefficient (R) of 0.681 indicates a significant relationship between the two variables. The determination coefficient value (R²) of 0.463 showed that the demonstration method had an influence of 46.3% on student activity, while the rest was influenced by other factors.